Development of a new Pellet-Clad Mechanical Interaction (PCMI) model and its application in ATFs. (June 2017) - Deng, Yangbin; Wu, Yingwei; Qiu, Bowen; Zhang, Dalin; Wang, Mingjun; Tian, Wenxi; Qiu, Suizheng; Su, G.H.
Highlights: A non-rigid Pellet-Clad Mechanical Interaction model was independently developed. The FROBA-ROD code was modified to perform the behavior simulation for ATFs. The applicability and reliability of the modification was validated. The modified code was used to perform the simulation for the ATF with SiC cladding. Abstract: In this study, a non-rigid Pellet-Clad Mechanical Interaction (PCMI) calculation model was independently developed with the consideration of plenum spring. Based on the new PCMI model, the FROBA-ROD code initially developed for conventional fuel rods was modified to perform the behavior simulation for accident tolerant fuels (ATFs). The applicability and reliability of the modification was validated by the result comparison with a public reference. The influence of rigid/non-rigid PCMI model was investigated by the comparison of results obtained by the initial and modified FROBA-ROD. It was found that for conventional fuel element, the rigid hypothesis was reasonable to some extent while was not applicable any more for PCMI simulation of ATFs with ceramic claddings. The modified FROBA-ROD was used to perform the calculation for both the traditional fuel rod and the ATF with SiC cladding. The result indicated that the low creep rate of SiC clad can delay the gap closure and PCMI effectively, but also lead to a much higher contact pressure and a possible brittle rupture. In addition, the delayed gap closure resulted in a higher fuel temperature, a higher fission gas release fraction and a higher inner gas pressure.